THE IMPLEMENTATION OF SYNCHRONOUS AND ASYNCHRONOUS E- LANGUAGE LEARNING IN EFL SETTING: A CASE STUDY - Rika Riwayatiningsih; Sulistyani Sulistyani (Universitas Putera Batam, 2020)
Teaching and learning process since the pandemic time has shifted away from the traditional face to face classroom into online distance learning, and this will be undergo in the post pandemic. This case study aimed to investigate the effectiveness use of the combined modes of synchronous and asynchronous in e- language learning for university students. While both types of that learning approach have its importance in different scenario. The research questions to be answered in the study was how the adoption of synchronous (discussion activity platform) and asynchronous (learning content platform) would be more effective in e- language learning. 55 university participants from the second semester of English Department who joined the online creative writing class in synchronous and asynchronous language learning activity received the survey questionnaire as the sampling of the collected data. The data from the interview was also obtained to get the learners insights regarding the course experiences.The results showed that the applying of the combination approach in online learning has been greatly effective in helping the learners in terms of the community interaction and material engagement. Moreover, the learners’ response about the using blended mode of synchronous and asynchronous for their learning is very positive. Some suggestions to enfold the problems over the online learning are also provided.